Politisasi Hadis Era Pilpres: Framing Simantik Hadis-Hadis Politik - Mugy Nugraha; Fatihunnada Fatihunnada; Nalil Huda (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Among the political machines used by Prabowo's supporters is the hashtag #2019gantipresiden which has gone viral on sosial media, and has even become a news portal on an online site with the address www.2019gantipresiden.org. The researcher found three posts published by the portal raising political issues and basing opinions on the hadith of the prophet. One of these hadiths is